Maternal weight, gut microbiota, and the association with early childhood behavior: the PREOBE follow-up study - Ana Nieto-Ruiz; Tomás Cerdó; Belén Jordano; Francisco J. Torres-Espínola; Mireia Escudero-Marín; María García-Ricobaraza; Mercedes G. Bermúdez; José A. García-Santos; Antonio Suárez; Cristina Campoy (BMC, 2023)
Abstract Background and aim Maternal overweight and breastfeeding seem to have a significant impact on the gut microbiota colonization process, which co-occurs simultaneously with brain development and the establishment of the "microbiota-gut-brain axis", which potentially may affect behavior later in life. This study aimed to examine the influence of maternal overweight, obesity and/or gestational diabetes on the offspring behavior at 3.5 years of age and its association with the gut microbiota already established at 18 months of life. Methods 156 children born to overweight (OV, n = 45), obese (OB, n = 40) and normoweight (NW, n = 71) pregnant women participating in the PREOBE study were included in the current analysis. Stool samples were collected at 18 months of life and gut microbiome was obtained by 16S rRNA gene sequencing. Behavioral problems were evaluated at 3.5 years by using the Child Behavior Checklist (CBCL). ANOVA, Chi-Square Test, ANCOVA, Spearman's correlation, logistic regression model and generalized linear model (GLM) were performed. Results At 3.5 years of age, Children born to OV/OB mothers showed higher scores in behavioral problems than those born to NW mothers. Additionally, offspring born to OB mothers who developed gestational diabetes mellitus (GDM) presented higher scores in attention/deficit hyperactivity and externalizing problems than those born to GDM OV/NW mothers. Fusicatenibacter abundance found at 18 months of age was associated to lower scores in total, internalizing and pervasive developmental problems, while an unidentified genus within Clostridiales and Flavonifractor families abundance showed a positive correlation with anxiety/depression and somatic complaints, respectively. On the other hand, children born to mothers with higher BMI who were breastfed presented elevated anxiety, internalizing problems, externalizing problems and total problems scores; likewise, their gut microbiota composition at 18 months of age showed positive correlation with behavioral problems at 3.5 years: Actinobacteria abundance and somatic complaints and between Fusobacteria abundance and withdrawn behavior and pervasive developmental problems. Conclusions Our findings suggests that OV/OB and/or GDM during pregnancy is associated with higher behavioral problems scores in children at 3.5 years old. Additionally, associations between early life gut microbiota composition and later mental health in children was also found.